2017
DOI: 10.16965/ijar.2017.298
|View full text |Cite
|
Sign up to set email alerts
|

STUDY OF ABSENCE OF 4Th TENDON OF FLEXOR DIGITORUM BREVIS MUSCLE

Abstract: Background: Flexor digitorum brevis is an intrinsic muscle of the sole of foot that lies immediately deep to central part of plantar aponeurosis.The flexor digitorum brevis divided into four tendons for lateral four toes. Each tendon is divided into two slips at base of proximal phalanx, to allow the flexor digitorum longus tendons and get inserted on both sides of the shaft of middle phalanx. It helps to reinforce arch of foot by flexing the proximal interphalangeal and metatarsophalangeal joints of the later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Clinical and cadaveric studies reported the incidence of the absence of the FDB's of one of its tendons of 72% [6] and 74% [8], respectively. Nathan and Gloobe reported that in 23% of their cases, a part of muscle and tendon inserting the fifth toe was absent, and in 3% of cases inserting in the fourth and fifth toe was absent [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical and cadaveric studies reported the incidence of the absence of the FDB's of one of its tendons of 72% [6] and 74% [8], respectively. Nathan and Gloobe reported that in 23% of their cases, a part of muscle and tendon inserting the fifth toe was absent, and in 3% of cases inserting in the fourth and fifth toe was absent [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies found that the missing tendon was replaced by an extra muscle originating from the calcaneal tuberosity with connections extending to the tendinous plate of the flexor digitorum longus and the quadratus plantae in a 75-year-old male cadaver [13]. Clinical and cadaveric studies reported the incidence of the absence of the FDB's of one of its tendons of 72% [6] and 74% [8], respectively. Nathan and Gloobe reported that in 23% of their cases, a part of muscle and tendon inserting the fifth toe was absent, and in 3% of cases inserting in the fourth and fifth toe was absent [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation